Human Resources Analysis Based on Total Quality Management in Improving Management Educational Process - Marzuki, Marzuki (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to analyze human resources based on Total Quality Management in improving management educational process. Total Quality Management (TQM) is an approach that focuses on quality in all aspects of an organization's operations, including human resources. In an educational context, this can help improve the effectiveness of the learning process and overall school management. This research uses qualitative research with a focus on Library Research. The data collection method is carried out through documentation. The data used is secondary data with data sources obtained from books and journals that discuss human resources, Total Quality Management and education management. Data analysis was carried out using Content Analysis. Based on the description, research results show that human resource analysis based on Total Quality Management (TQM) is important in improving the management educational process in educational institutions seen from the aspects of recruitment and selection, professional development, performance assessment, quality awareness, performance awards. The contribution of TQM in improving management educational processes is also very important from customer aspects (stakeholder) orientation, process understanding, continuous improvement, fact-based management, training and development, and systems approach. Based on these findings, it can be concluded that improving educational management requires good management so that educational goals are achieved. Apart from good management, adequate human resources are also needed so that they can carry out the existing educational vision and mission.